Analisis Potensi Dan Peluang Pengembangan Usaha di Bumdes “E Mas Jaya” Desa Banyuputih, Kecamatan Wringin, Kababupaten Bondowoso: Penelitian - Mohammad Imron; Miftahus Surur; Yesi Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the potential and business development opportunities of BUMDes “E Mas Jaya” in Banyuputih Village, Wringin District, Bondowoso Regency. BUMDes plays an important role in improving community welfare through the management of local resources. The research employed a qualitative descriptive method with a case study approach, using interviews, field observations, and documentation involving BUMDes managers, village officials, and local communities. SWOT analysis was applied to identify strengths, weaknesses, opportunities, and threats. The findings indicate that BUMDes has great potential in agriculture and agricultural trade but faces constraints in capital and management. Development opportunities include product diversification, external collaboration, and the use of information technology in marketing. With proper management strategies, improved human resource capacity, and support from government and private sectors, BUMDes “E Mas Jaya” has strong prospects to significantly contribute to the village economy.